Retargeting of Herpes Simplex Virus (HSV) Vectors - Goins, William F. (Curr Opin Virol, 2016)
Gene therapy applications depend on vector delivery and gene expression in the appropriate target cell. Vector infection relies on the distribution of natural virus receptors that may either not be present on the desired target cell or distributed in a manner to give off-target gene expression. Some viruses display a very limited host range, while others, including herpes simplex virus (HSV), can infect almost every cell within the human body. It is often an advantage to retarget virus infectivity to achieve selective target cell infection. Retargeting can be achieved by (i) the inclusion of glycoproteins from other viruses that have a different host-range, (ii) modification of existing viral glycoproteins or coat proteins to incorporate peptide ligands or single-chain antibodies (scFvs) that bind to the desired receptor, or (iii) employing soluble adapters that recognize both the virus and a specific receptor on the target cell. This review summarizes efforts to target HSV using these three strategies.